Absorption coefficient and transmission loss measurements of acoustics materials using sound intensity technique - 393759 Gowri M. Govindarajan (Kuala Lumpur : UTM, 1996)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1996